Systematic Literature Review: The Effectiveness of Socio-Scientific Problem-Based Learning Models in Chemistry Learning - Asmaul Husna; Nabila Yasmin; Miterianifa (Universitas Pendidikan Mandalika, 2025)
This study is a systematic literature review (SLR) that aims to analyze the effectiveness of the integrated Socio-Scientific Issues (PBL) Problem-Based Learning (PBL) model or PBL-SSI in improving students' scientific abilities in chemistry learning in secondary school. The background of this research is the dominance of traditional lecture methods that fail to strengthen 21st century critical thinking and skills, demanding a change in a more contextual and participatory approach. The SLR procedure follows systematic, transparent, and replicable guidelines, with literature searches via Google Scholar (time range 2020–2025) using the keyword